The Pucok Reubong Motif as an Inspiration for Leather Bag Design - Alaina, Syifa; Izzati, Fauziana; Sembiring, Sartika Br (Institut Seni Indonesia Padang Panjang, 2024)
The pucok reubong motif has been stylised from the form of young bamboo shoots. These bamboo shoots are transformed into a unique decorative pattern. The artist's interest in exploring the pucok reubong motif stems from its distinct shape, surrounded by triangular leaves with pointed ends resembling swords, and its interlocking patterns. This inspired the artist to incorporate the pucok reubong motif into leather bag designs. The creative process follows the Hendriyana method, which consists of four main stages: (1) pre-design, which involves the development of imagination; (2) design, where alternative designs are visually conceptualized; (3) realization, in which selected sketches are transformed into final works; and (4) presentation, involving exhibitions to establish communication between the artist and art enthusiasts. The concept applied is a symbolic expression, representing modern art that utilizes traditional idioms as its foundation. In the final project titled “Pucok Reubong Motif as an Idea for Leather Bag Creation”, the artist applied the pucok reubong motif as a decorative element on leather bags. This work aims to enhance aesthetic appeal while introducing the pucok reubong motif to a wider audience unfamiliar with it. The bags were created using embossing techniques combined with weaving, resulting in works that are both artistic and meaningful.